How Sweet Is This? A Review and Evaluation of Preoperative Carbohydrate Loading in the Enhanced Recovery After Surgery Model. (21st October 2019) - Ackerman, Robert S.; Tufts, Christopher W.; DePinto, David G.; Chen, Jeffrey; Altshuler, Jaclyn R.; Serdiuk, Andrew; Cohen, Jonathan B.; Patel, Sephalie Y.
Abstract: Preoperative carbohydrate loading is a contemporary element of the enhanced recovery after surgery (ERAS) paradigm. In addition to intraoperative surgical and anesthetic modifications and postoperative care practices, preoperative optimization is essential to good postsurgical outcomes. What was long held as dogma, a period of prolonged fasting prior to the administration of anesthesia, was later re‐examined and challenged. Along with the proposed physiologic effects of decreasing the surgical stress response and insulin resistance, preoperative carbohydrate loading was also demonstrated to improve patient satisfaction and well‐being, without an increase in perioperative complications. The benefits are most strongly observed in abdominal and cardiac surgery patients, but there has also been data which support its use in other specialties and surgeries. Barriers to the adoption of perioperative carbohydrate loading are few, but importantly include overcoming the inertia to modify older and more restrictive fasting guidelines and achieving the multidisciplinary consensus necessary to implement such changes. Despite these challenges, and with an existing body of evidence supporting its benefits, preoperative carbohydrate loading presents a significant contribution to the ERAS programs.